The position of the Turkish and Moroccan second generation in Amsterdam and Rotterdam : the TIES study in the Netherlands - Crul, Maurice; Heering, Liesbeth (IMISCOE research., 2008)
First publication of the TIES Project studies the social situation and views of the Dutch second generation of Turkish and Moroccan origin.